Effect of Biomass-Based Catalyst in Walnut Shell/Polypropylene to BTX - Guo, Yanan; Pan, Xin; Zhu, Qingjiao; Ma, Jingjing; Guo, Qingjie (Fine Chemical Engineering, 2021)
Four biomass-based catalyst carriers with different pore structures were prepared by using a carbonization-activation method, followed by employment in the copyrolysis of Walnut Shell/Polypropylene (WNS/PP) to produce Benzene, Toluene and Xylene (BTX). Ten cycles were performed in each copyrolysis test in a bench-scaled tube furnace to determine the suitable pore size of the catalyst and excellent cycling performance for BTX production. In addition, Zn, Ni, and Ce were loaded with the selected catalyst carriers to synthesize the most suitable biomass-based catalyst. Results showed that the pore size and active center of the catalyst were the key factors affecting the WNS/PP catalytic copyrolysis. Biomass-based carrier with a pore size in the range of 0.55-1.2 nm was the most suitable to produce BTX in the optimal 10 cycle performance; it realized a relative BTX content of 9-20 area%, and a BTX mass yield of 23-67 mg/(graw) in the liquid-phase products from the WNS/PP copyrolysis. A catalyst loaded with 10 wt% Zn possessed the best catalytic effect with a relative BTX content of 39.49 area%, and a BTX yield of 111.13 mg/(graw).